Continuous toolpath planning in a graphical framework for sparse infill additive manufacturing. (October 2020) - Gupta, Prashant; Krishnamoorthy, Bala; Dreifus, Gregory
Abstract: We develop a framework that creates a new polygonal mesh representation of the sparse infill domain of a layer-by-layer 3D printing job. We guarantee the existence of a single, continuous tool path covering each connected piece of the domain in every layer in this graphical model. We also present a tool path algorithm that traverses each such continuous tool path with no crossovers . The key construction at the heart of our framework is a novel Euler transformation which converts a 2-dimensional cell complex K into a new 2-complex K ˆ such that every vertex in the 1-skeleton G ˆ of K ˆ has even degree. Hence G ˆ is Eulerian, and an Eulerian tour can be followed to print all edges in a continuous fashion without stops. We start with a mesh K of the union of polygons obtained by projecting all layers to the plane. First we compute its Euler transformation K ˆ . In the slicing step, we clip K ˆ at each layer using its polygon to obtain a complex that may not necessarily be Euler. We then patch this complex by adding edges such that any odd-degree nodes created by slicing are transformed to have even degrees again. We print extra support edges in place of any segments left out to ensure there are no edges without support in the next layer above. These support edges maintain the Euler nature of the complex. Finally, we describe a tree-based search algorithm that builds the continuous tool path by traversing "concentric" cycles in the Euler complex. Our algorithm produces a tool path that avoids material collisions and crossovers, and can be printed in a continuous fashion irrespective of complex geometry or topology of the domain (e.g., holes). We implement our test our framework on several 3D objects. Apart from standard geometric shapes including a nonconvex star, we demonstrate the framework on the Stanford bunny. Several intermediate layers in the bunny have multiple components as well as complicated geometries. Graphical abstract: Highlights: New method to generate continuous toolpaths with no crossovers in sparse infill AM. Employs Euler Transformation of general polyhedral complexes. Handles most domains with complex geometry/topology in layer-by-layer printing. Method validated on simple and complex print domains.